A prediction model incorporating the BRAFV600E protein status for determining the risk of cervical lateral lymph node metastasis in papillary thyroid cancer patients with central lymph node metastasis. Issue 11 (November 2021) - Liu, Shiyang; Liu, Chenguang; Zhao, Lu; Wang, Kun; Li, Shuyu; Tian, Yao; Jiao, Bo; Gui, Zhengwei; Yu, Tianyao; Zhang, Lin
Abstract: Background and objectives: Cervical lateral lymph node metastasis (LLNM) is a predictor of poor prognosis for papillary thyroid carcinoma (PTC) patients. However, the risk factors for LLNM remain unclear. The purpose of the study was to examine the risk factors for LLNM and construct a prediction model. Methods: With Ethics Committee approval, a total of 1198 PTC patients were retrospectively included in our study. Univariate and multivariate analyses were performed to explore the relationship between clinicopathological characteristics and LLNM. A nomogram for predicting LLNM in PTC patients with central lymph node metastasis (CLNM) was constructed and validated. Results: The negative BRAF V600E protein expression was significantly correlated with positive LLNM status in PTC patients. In PTC patients with CLNM, the number of metastatic central lymph nodes (LNN) ≥ 3 and the ratio of metastatic central lymph nodes (LNR) ≥ 0.565 were found to be significantly associated with positive LLNM status. The nomogram for predicting LLNM risk in PTC patients with CLNM incorporated four risk factors: tumor size, the BRAF V600E protein expression, LNN and LNR. The prediction model showed excellent discrimination, with a C-index of 0.714. Conclusions: The negative BRAF V600E protein expression was more likely to lead to LLNM. LNN ≥3 and LNR ≥0.565 were associated with LLNM risk in PTC patients with CLNM. Our nomogram might assist clinicians in developing individual suitable follow-up strategies for PTC patients with CLNM.